The Relationship Between Nurse Caring and Anxiety Levels in Preschool Children During Hospitalization in the Pediatric Ward - Widyawati, Mei; Dini, Tiara Putri Ryan; Hakim, Lukman; Basuki, Hyan Oktodia; Nurhadi, Muhammad; Khalimah , Niswatul (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Pre-school children often see the experience of hospitalization as something scary. they still have difficulty distinguishing between imagination and reality, so that they often think that hospital treatment is a form of punishment for their behavior. especially while the child is undergoing treatment in hospital, usually children will be prohibited from moving around a lot and must get plenty of rest. This is certainly disappointing for the child, because he didn't have much time to play actively in the hospital. This can increase anxiety in children. The purpose of this study was to determine the relationship between nursing care and anxiety levels in preschool children during hospitalization in the pediatric ward of RSNU Tuban. Methods: This study uses a non-experimental analytical design with a cross-sectional approach. The sample of this study consisted of all parents of preschool children who were hospitalized in the pediatric room of RSNU Tuban in February-March 2025, totaling 56 respondents. By using non-probability sampling with accidental sampling technique and data analysis was carried out using the sperm rank test. Results: The results of the study analyzed the relationship between nurse caring and anxiety levels in preschool children during hospitalization in the Pediatric Ward of RSNU Tuban. This was proven by analyzing the Speramen Rank test of -0.401 and p 0.002, which means the coefficient value is moderate, which can be concluded that H1 is accepted. Conclusion: The results of this study identified that nursing care can reduce the level of anxiety in preschool children during hospitalization, as evidenced by the better the nursing care provided, the lower the level of anxiety in preschool children.